TANGGUNG JAWAB ORANGTUA TERHADAP ANAK UNTUK MEMBERIKAN PERLINDUNGAN BERDASARKAN UNDANG-UNDANG NOMOR 35 TAHUN 2014 TENTANG PERLINDUNGAN ANAK - Muzayanah, Muzayanah (Jurnal Pengabdian Kepada Masyarakat Media Ganesha FHIS, 2022)
Community Service Activities are the implementation of the Tridharma of Higher Education that must be carried out in order to provide understanding to the community in this case to the residents of Prolanis (the Elderly and Chronic Disease Program) which is managed by the Primary Clinic "RAHMATIKA" located in Pengkol hamlet Rt.05/Rw. 01, Mangunsari Village, Gunung Pati District, Semarang City. This service activity is a continuous and programmed activity and is carried out by providing counseling for residents of Prolanis patients in the field of education about "Parental Responsibilities to Children to Provide Protection Based on Law Number 35 of 2014 concerning Child Protection". In a family, of course, we find children in the family. Children are an inseparable part of human survival and the sustainability of a nation and state. In order to be able to be responsible for the sustainability of the nation and state, every child needs to get the widest opportunity to grow and develop optimally, physically, mentally, and socially. For this reason, it is necessary to make efforts to protect children's welfare by providing guarantees for the fulfillment of their rights without discriminatory treatment. The state upholds human rights, including the human rights of the child, which is marked by the guarantee of protection and fulfillment of children's rights in the 1945 Constitution of the Republic of Indonesia as well as several provisions of laws and regulations both national and international. This guarantee is strengthened through the ratification of the International Convention on the Rights of the Child, namely with the ratification of the Convention on the Rights of the Child through Presidential Decree Number 36 of 1990 concerning Ratification of the Convention on the Rights of the Child. Problems often occur related to the emergence of several cases that have recently been very widely reported, regarding sexual crimes against children, pedophilia, violence against children, murder of children by their parents and many other cases that may occur but have not been revealed. Cases that often occur are for example the exploitation of children in the economic field, which we often see children living on the streets and wandering around to beg or beg at light intersections, at crossroads and so on. The next question is whether the residents of Prolanis Clinic "RAHMATIKA" Semarang City in general already know about Law Number 35 of 2014 concerning Child Protection ?. Considering that the Child Protection Law is relatively new, there are still many people who do not know or even know what the contents of this new Child Protection Law are. Given the very importance of Law Number 35 of 2014 concerning Child Protection, it is the responsibility of parents to children to provide protection for their children. So that parents understand about this Child Protection Law, it is hoped that by knowing and understanding this law, especially for parents to be more careful and always protect the children in their environment, so that children will be protected from crimes that often occur. committed by perpetrators of crimes that are often committed by adults.